Making collapsing pulse user-friendly - Thomas, Puthiaparampil T. (2020)
Collapsing pulse is generally elicited by elevating the patient’s arm. However, the pulse becoming stronger on arm elevation is a physiological phenomenon, which is bound to create confusion, if routine lifting of the arm in search of collapsing pulse is practiced. The name ‘collapsing pulse’ represents only the second component of this sign. It masks the more important first component - the slapping, bounding upstroke, characterised by its other name ‘water-hammer pulse’. It is possible to elicit this sign by appreciating the slapping character on routine pulse examination. The insistence on arm lifting in medical school teaching is better avoided.